1932
DOI: 10.1098/rspb.1932.0008
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline vitamin D

Abstract: In two earlier papers in these ‘Proceedings’ (Askew et al ., 1930, a ; Angus et al ., 1931) a crystalline antirachitic substance was described, obtained by vacuum distillation of the products of irradiation of ergosterol. In the second paper, the physical properties and antirachitic activities of a number of successive preparations of this product were recorded, and it was shown that these were sufficiently constant to suggest that it cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1936
1936
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…In 1903, Niels Finsen was awarded the Nobel Prize in Physiology or Medicine for his discovery that shortwave UV light was effective in the treatment of cutaneous TB (28) . Vitamin D 2 was purified and crystallised in 1931 (29) and Charpy subsequently pioneered the use of pharmacologic doses ( ‡1 . 25 mg daily) of vitamin D 2 to treat cutaneous TB (30) .…”
Section: Vitamin D and Tuberculosis: Historical Aspectsmentioning
confidence: 99%
“…In 1903, Niels Finsen was awarded the Nobel Prize in Physiology or Medicine for his discovery that shortwave UV light was effective in the treatment of cutaneous TB (28) . Vitamin D 2 was purified and crystallised in 1931 (29) and Charpy subsequently pioneered the use of pharmacologic doses ( ‡1 . 25 mg daily) of vitamin D 2 to treat cutaneous TB (30) .…”
Section: Vitamin D and Tuberculosis: Historical Aspectsmentioning
confidence: 99%
“…They subsequently reported that heated oxidised cod-liver oil could not prevent xerophthalmia but could cure rickets in rats, and concluded that "fatsoluble factor A" consisted of two entities, one which could prevent xerophthalmia (subsequently called vitamin A) and one which cured rickets (subsequently called vitamin D, as the terms vitamin B and vitamin C had already been coined) [ 59 ] . Vitamin D 2 was puri fi ed and crystallised in 1931 [ 60 ] , and Charpy subsequently pioneered the use of pharmacological doses ( ³ 1.25 mg or 50,000 IU daily) of vitamin D 2 to treat cutaneous TB [ 61 ] . Vitamin D 2 was also used to treat pulmonary TB, both as a single agent and, following the introduction of effective anti-tuberculous chemotherapy, as an adjunct to antibiotic treatment.…”
Section: Historical Studiesmentioning
confidence: 99%
“…That vitamin D itself, however, is toxic when given in large enough amounts, is borne out by the fact that the pure crystalline vitamin D2 (calciferol) has been shown to be toxic for experimental animals (17) and man (20).…”
Section: Discussionmentioning
confidence: 99%
“…In 1932 Askew and his associates succeeded in isolating pure vitamin D from crude irradiated ergosterol and named it " calciferol " (17). Their product was crystalline and had a potency of 40,000 international vitamin D units per milligram.…”
mentioning
confidence: 99%
See 1 more Smart Citation